2004
DOI: 10.1111/j.1540-4609.2005.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Intellectual Property Concepts into MIS Education: An Empirical Assessment*

Abstract: The evolving legal environment surrounding intellectual property (IP) and its impact on information systems, especially involving electronic commerce, and the type of education and training provided by management information systems (MIS) faculty to MIS students is a relationship that has not been investigated. Although organizations are confronted with IP infringement actions dealing with copyright, trademark, and their relationship to information systems, these issues are not adequately dealt with in MIS cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…They concluded that TPB provided more useful information for information systems development. Mykytyn, Mykytyn, and Harrison (2005) used TPB to examine the integration of intellectual property concepts into information systems education.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…They concluded that TPB provided more useful information for information systems development. Mykytyn, Mykytyn, and Harrison (2005) used TPB to examine the integration of intellectual property concepts into information systems education.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…It has also been noted that IS academia has done a less than desirable job of integrating business-related issues such as patents and other forms of intellectual property into undergraduate MIS degree programs (P. P. Mykytyn, Mykytyn, & Harrison, 2005). This study will alert managers that IS academia is attentive to the changing nature of the patent landscape and that the community is committed to providing relevant research which will make its way to the classroom.…”
Section: Implications For Practicementioning
confidence: 87%
“…The rapid growth of e-crime and apparent lack of security awareness suggest that education programs for e-commerce professionals do not provide sufficient preparation for preventing e-commerce legal and security problems. Research has documented inadequate coverage of security (Kim et al 2005;Morrison and Oladunjoye 2002) and legal (Mykytyn, Mykytyn, and Harrison 2005) issues in e-commerce education programs. The present study addresses the apparent gap between the seriousness of e-commerce risks and the preparation provided to those planning careers in the field.…”
Section: E-crime Prevention: An Investigation Of the Preparation Of Ementioning
confidence: 98%
“…It is therefore essential that e-Crime Prevention 3 e-commerce education includes emphasis on prevention topics. The present study builds on the literature to identify prevention topics concerning e-commerce: law (Gueldenzoph 2006;Mykytyn et al 2005); ethics (Adam, Aderet, and Sadeh 2007;Bruce and Edgington 2008), and security (Gunasekaran and Ngai 2004;Kim et al 2005;Ragothaman, Lavin, and Davies 2007). Certainly, other activities in e-commerce may contribute to loss prevention.…”
Section: Regulatory Focus Theory and E-commercementioning
confidence: 99%